(untitled) (Central Medical College Journal, 2022)
Chest CT scans of 200 symptomatic patients infected with COVID 19 from different health facilities and home were reviewed for common CT findings in relationship with their clinical symptoms, comorbidities and the time between symptom onset and the initial CT scan was studied in this cross-sectional study. Cases were categorized into three groups according to the timing of HRCT, 10 cases were in early (0-2days), 56 cases in intermediate (3-5days) and 110 cases were in late (6-12days) groups. Chest CT scan images showed bilateral peripheral ground glass opacities 96.63%, pulmonary consolidations 15.9%. Notably 29.54% patient had normal CT scan chest and 60% of them were imaged at early phase. With a longer duration of symptoms, chest CT findings were more typical including GGO, consolidation with greater total lung involvement. Bilateral peripheral GGO was observed in 20% patients at early phase while 53.57% and 64.54% were observed at intermediate and late phase of illness. Among the symptoms cough and dyspnea were observed more related with typical CT changes (95%). Diabetes and Hypertension (58% of patients) were the leading comorbidities that were found related with GGO and other typical CT findings. Mean time duration between symptom onset and positive RT PCR, CT scan changes were 4.79 and 7.55 respectively. Central Medical College Journal Vol 5 No 2 Jul 2021 PP 70-75